Thermal conductivity of diamond/Ag composites with chromium carbide coated diamonds for the building materials of high power modules. (July 2014) - Zhao, C.; Gao, J. Z.
Abstract : This paper reports on a study of the preparation and characterisation of diamond/Ag composites for the building materials of high power modules. The Cr7 C3 coated diamond particles are utilised to improve the interfacial bonding between the Ag and diamond and composites are prepared by hot pressing technique. The characteristics of Cr7 C3 coating layers were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The results show that the Cr7 C3 coatings on the diamonds result in a strong interfacial bonding and a greatly enhanced thermal conductivity of the composites. A largely enhanced thermal conductivity of 768 W m −1 K −1 is obtained in Cr7 C3 coated composites, which increases 168% relative to that of uncoated composites at 65% diamond volume fraction. The measured thermal conductivity agrees reasonably well with the predictions by a differential effective-medium (DEM) model.